Possibilities of Integrated Assessment of Functional State of Organism for Control of Therapy Efficacy and Predicting Outcomes in Pregnancies in Women with Preeclampsia of Varying Severity - V.I. Cherniy; V.S. Kostenko; A.V. Sidorenko (Zaslavsky O.Yu., 2012)
In order to objectify clinical evaluation parameters of the functional state of the body of pregnant women with preeclampsia and evaluate the effectiveness of the therapy 122 women had been examined. The heart rate variability (HRV) parameters in relation to the types of central hemodynamics had been studied. The superslow brain potentisl - the omega-potential as an indicator of the level of the central regulation of heart rate and heart rate variability parameters of nonlinear dynamics - α1 as parameter of detrended fluctuation analysis (DFA). Correlation between the dynamics of the studied parameters and pregnancy outcome had been marked - if favorable response to the therapy, gestational age and the number of natural childbirth increased. This dependence presents investigated parameters as predictors of pregnancy complications and as indicators of the efficacy of the therapy. As a result of the treatment, the complex of indices being studied was combined into a single structure - a matrix of adaptation of functional systems of pregnant women to gestational pathological factors.